Morphodynamic assessment of the Volta Delta using Space-Borne remote sensing - Kwadzo, Brempong Emmanuel (University of Cape Coast, 2023)
The stability and sustainability of deltas around the world are endangered by pressing global problems including sea level rise, land subsidence, erosion, biodiversity loss, urbanization, and climate change, requiring harmonized and collaborative strategies for effective mitigation. Over the past decade, the Volta Delta in Ghana has experienced adverse consequences of these impacts, including recurrent and accelerated flooding and erosion as well as the loss of valuable wetland ecosystems. This study focused on analyzing the changes in the delta's morphodynamics using remote sensing approaches. This study employs the use of satellite-based SAR-Interferometry, Extreme Coastal Water Levels (ECWL), and Pleiades stereo images to estimate land subsidence rates and the extent of coastal flooding in the Volta Delta of Ghana. The results from the study revealed that the Keta Lagoon and Songor Lagoon areas located immediately at both the east and west of the Volta Delta exhibit varying rates of subsidence, reaching up to 4 mm/yr and about 20% of the entire Volta Delta, including vulnerable sand barriers, could be sited below the mean sea level. Furthermore, almost 40% of the Keta area is susceptible to flooding including significant sites like beach resorts and historical landmarks with the wave runup as the primary contributing factor. The study underscores the importance of creating a robust monitoring framework to regularly assess the conditions in the Volta Delta and West Africa, facilitating a better understanding of delta dynamics, identification of key drivers, and the generation of essential data for future research and early warning systems, all critical for long-term resilience.
xxii,221p;, ill
Keywords: Coastal Flooding Digital Elevation Model FABDEM InSAR Persistent Scatter Interferometry (PS-InSAR) Relative sea level rise (RSLR) Sea level Rise (SLR) Sentinel 1 Subsidence Wave run-up